The Health Impact of Extreme Weather Events in Sub-Saharan Africa - Wang, Limin (The World Bank, 2009)
Extreme weather events are known to have serious consequences for human health and are predicted to increase in frequency as a result of climate change. Africa is one of the regions that risks being most seriously affected. This paper quantifies the impact of extreme rainfall and temperature events on the incidence of diarrhea, malnutrition and mortality in young children in Sub-Saharan Africa. The panel data set is constructed from Demographic and Health Surveys for 108 regions from 19 Sub-Saharan African countries between 1992 and 2001 and climate data from the Africa Rainfall and Temperature Evaluation System from 1980 to 2001. The results show that both excess rainfall and extreme temperatures significantly raise the incidence of diarrhea and weight-for-height malnutrition among children under the age of three, but have little impact on the long-term health indicators, including height-for-age malnutrition and the under-five mortality rate. The authors use the results to simulate the additional health cost as a proportion of gross domestic product caused by increased climate variability. The projected health cost of increased diarrhea attributable to climate change in 2020 is in the range of 0.2 to 0.5 percent of gross domestic product in Africa